Nitretação a plasma de aço inoxidável austenítico sinterizado com fluxo pulsado de nitrogênio - Pereira, Diandra Grossmann (2022)
Sintered stainless steels represent an important part of powder metallurgy and surface treatments are performed on these materials with the aim of increasing surface hardness and resistance to wear and corrosion. However, the high level of residual stress of these layers can sometimes lead to the formation of cracks in nitrided surfaces of sintered stainless steel. In a study carried out at UTFPR, it was possible to control the nitrogen concentration in the nitrided layers of stainless steel, using gas pulses in the nitrogen flow. Thus, the present work aimed to control the formation of cracks in sintered stainless steel samples, using gas pulses during nitriding. For this, sintered AISI 316L stainless steel samples were nitrided under pulsed flow of nitrogen under different pulse conditions. The surfaces of the samples were evaluated by the formation of cracks in an optical microscope and in a scanning electron microscope. X-ray diffraction measurements were also performed for phase detection and analysis of austenite expansion. The analysis of the microstructure in profile helped in the evaluation of the formation of the layers and to locate the preferred regions of crack formation. Hardness measurements were performed to characterize the treated surfaces. The effect of the sintering temperature was also evaluated, and the samples were previously sintered at three temperatures. The hardness results show that for longer times and with pulses with a longer time of nitrogen on, the hardness presented higher values, showing the possibility of controlling the nitrogen concentration by the processing parameters. The comparison of samples from nitriding cycles under continuous flow and pulsed flow of nitrogen indicates that it is possible to reduce the formation of cracks. X-ray diffractograms show that samples treated under pulsed flow had less expansion of the crystal lattice (expanded austenite), which is directly related to the nitrogen concentration and, therefore, to the residual stresses of the layer.